Mechanical constitutive model of stand off damping composites layered rubber core under wide strain rates - Zhangda Zhao; Wenjun Meng; Bijuan Yan; Guansen Qiao; Yuan Qin; Yao Wang; Tao Yang; Hong Ren (Scientific Reports)
Abstract To characterize the dynamic mechanical response and vibration-damping characteristics of a layered rubber core (LRC) in a stand-off damping structure, a series of experiments were carried out and a continuous power-law variable fractional-order Kelvin–Voigt constitutive model (VFKV) is proposed in this study. The nonlinear elastic behaviors of LRC under wide strain rate are fitted by the hyperelastic and the viscoelastic constitutive model, respectively. Firstly, based on the assumption of continuum mechanics, the fitting abilities of six hyperelastic constitutive models, i.e., the modified Mooney-Rivlin model including M-R(2), M-R(3) and M-R(5), Yeoh model, Ogden(2) and Ogden(4) model are compared. Additionally, various integer-order viscoelastic constitutive models, including Maxwell, Kelvin–Voigt (K–V), Poynting–Thomson (P–T), Zener, and Burgers, and constant and variable fractional order viscoelastic constitutive models, were employed to fit and describe the constitutive characteristics of the LRC. Finally, the VFKV model was employed to assess the loss ability for LRC and single-layer rubber, which was validated through the energy method. This confirms the universal applicability of the model. It is concluded that the VFKV model have the highest and relatively stable fitting correlation values for all three LRCs and single-layer rubber, with a fitting deviation below 1%. Thus, this method provides assistance and guidance for the selection of constitutive model to characterize the mechanical behavior of rubber-like materials under wide strain rates. In addition, it can save engineering calculation time by eliminating the establishment of complex structural dynamics equations and interlayer motion transfer equations.